Recognition of anxiety disorder and depression and literacy of first-aid support: A cross-sectional study among undergraduate students in Ha Noi, Viet Nam 2018 - Nguyen Thai Quynh-Chi (Health Psychology Open, 2021)
This study is aimed at exploring undergraduate students’ abilities to recognize anxiety disorder and depression symptoms, and their literacy of mental first-aid supports for these problems. Using a mixed-method, cross-sectional design, data were collected from 724 undergraduate students in Hanoi. This used a questionnaire on literacy of anxiety disorder and depression, adapted from the Australian National Survey of Mental Health Literacy and Stigma. The prevalence of the respondents who could identify anxiety disorder and depression symptoms were 25.9% and 42.3%, respectively. Literacy of mental first-aid supports focused on: listening to the person in an understanding way, encouraging the person to be more active, seeking professional help, make appointment with the general doctor.